Racismo estrutural: episódios de discriminação racial na turma do 5o ano do ensino fundamental no Centro Municipal de Educação Básica Professora Lívia Lorene Bueno Maia em Arraias-TO - SANTOS, Delma Teixeira dos (Universidade Federal do Tocantins, 2025)
This work reports on structural racism through episodes of racial discrimination and the consequences generated in the 5th year elementary school class at the Centro Municipal de Educação Básica Professora Lívia Lorene Bueno Maia in Arraias-To. In which the objective of this research seeks to identify situations and episodes of structural racism in the 5th year of elementary school at a school in Arraias-To. The specific objectives emphasize: understanding the historical and theoretical conceptual foundations of the forms of racism present in Brazil and in Arraias-To, raising policies, laws and planning aimed at ethnic-racial education in elementary education in Brazil and the developments in the Municipal Center of Basic Education Professor Lívia Lorene Bueno Maia and contribute to reflection actions on various forms of racism at the Municipal Center for Basic Education Professor Lívia Lorene Bueno Maia and in the contemporary context. To carry it out, this research used a bibliographical survey of the history and concepts of structural racism in the school environment; of theses that describe the municipality of Arraias; documentary survey and secondary sources to characterize the municipality and the educational policies of the region and the school. In addition to analyzing through participant observation, through activities and dynamics promoted in the context of the supervised internship, the perceptions of the 5th year children and the teacher responsible for the class, interviews were carried out with the teacher and the pedagogical coordinator. Authors such as: Silvio Almeida (2019), Moreira (2020), Bersani (2020), Oliveira (2021), Crochík (2015), Candau (2008), Charlot (2002) and others were part of the theoretical basis of this work. However, the analysis of the results shows how the community goes through situations of racial violence by carrying out an activity with a 5th year class at the Municipal Center for Basic Education Professor Lívia Lorene Bueno Maia in Arraias – TO and it was noticed that the problems Related to racism range from recurrent bullying practices, prejudice and racial discrimination, episodes of individual and institutional racism, which are consequences of the normality of structural racism and which, reciprocally, provide conditions for the reproduction of the racist structure of Brazilian society. Therefore, this reality must continue to be problematized in future studies that build knowledge from a decolonial perspective that supports effective pedagogical actions towards anti-racist education that disrupts society as it has presented itself and soon inaugurates a more just and humane world.